Twentieth-century British and Irish poetry : Hardy to Mahon - O'Neill, Michael; O'Neill, Michael, 1953-; Callaghan, Madeleine (Chichester, West Sussex, U.K. ; Malden, MA : Wiley-Blackwell, 2011)
"Featuring contributions from some of the major critics of contemporary poetry, Twentieth-Century British and Irish Poetry offers an accessible, imaginative, and highly stimulating body of critical work on the evolution of British and Irish poetry in the twentieth-century. Covers all the poets most commonly studied at university level courses. Features criticisms of British and Irish poetry as seen from a wide variety of perspectives, movements, and historical contexts. Explores current debates about contemporary poetry, relating them to the volume's larger themes. Edited by a widely respected poetry critic and award-winning poet."--
"Twentieth-Century British and Irish Poetry offers an accessible and imaginative guide to the criticism of British and Irish poetry in the the twentieth century. The editors also supply their own stimulating readings of the poetry. Through an insightful narrative - which points up the major features of the poets and the chosen excerpt Michael O'Neill and Madeleine Callaghan knit together contributions by major critics, as well as essays by a number of distinguished poet-critics, including Geoffrey Hill, Andrew Motion, and Tom Paulin. Featured poets include Hardy, Yeats, Eliot, Owen, Lawrence, Auden, Dylan Thomas, Larkin, MacDiarmid, Stevie Smith, Plath, Heaney, Mahon and many others"--
Includes bibliographical references (p. [272]-289) and index.
Keywords: English poetry -- 20th century -- History and criticism; English poetry -- Irish authors -- History and criticism; Poetics -- History -- 20th century